A proposed strategic plan for Shakey's - Lizo, Vincent Troy (Animo Repository, 1996)
Shakeys began its operations in the Philippines in 1975. A San Miguel-owned corporation then, it immediately made an impact in the market as it grew from a single outlet in Makati to 28 outlets in 1987 when the Prieto group bought International Family Food Services, Inc. (IFFSI) and took over. Today, with over 90 franchise-owned restaurants and eight (8) IFFSI-owned units, it has been the market leader in the pizza segment of the quick service restaurant industry since the late 1970s. But despite its 45% share of the market in Metro Manila and its 1995 sales increase of 11.98%, its market position has been threatened by Pizza Hut during the last few years. Shakeys average sale per unit in 1995 of P 28, 575 is 44% lower than the Pizza Huts average of P 42, 500. Even though Shakeys stores increased from 95 to 106, its systemwide average sales decreased by 0.36%. Furthermore, in the 1995 Pulse Research Synfast Survey on Pizza restaurants, Shakeys patronage rate decreased from 54% in 1986 to 40% in 1990. Aside from Pizza Hut, Jollibees acquisition off Greenwich in May 1995 poses another threat to Shakeys objective of overtaking Shakeys and Pizza Hut in the year 2000 is not improbable. For Shakeys to maintain leadership, it has to come up with strategies that will place itself in a more defendable position against the competitive forces and threats that shapes the industry. In order to do so, Shakeys corporate strategy should be geared towards aggressive expansion through franchising. Although, Shakeys has been rapidly expanding during the last few years, it must shift its focus on the proliferation of smaller, down-sized restaurant units that offer limited product lines. Down-sized restaurants do not only entail a lower cost of investment, which makes it more attractive to prospective franchisees, but it will also brings down operating costs. It consonance with the expansion of down-sized units, Shakeys should also adopt strategies prevalent in fragmented industries like tightly managed decentralization, formula facilities and focusing on strong products. Its strategies must be able to hit a balance between implementing tight control measures to ensure consistent quality and service, and allowing franchisees some degree of autonomy and independence. Some of the functional strategies include the streamlining of standard operating procedures, the standardization of restaurant organizational structure, the establishment of a career development program, and improved product innovation and management.